RESPONS PERTUMBUHAN DAN PRODUKSI BAWANG SABRANG (Eleutherine americana Merr) TERHADAP PEMBELAHAN UMBI DAN PERBANDINGAN MEDIA TANAM - Dewi Sartika Siregar; Haryati Haryati; Toga Simanungkalit (Universitas Sumatera Utara, 2014)
Low bulb supply of bawang sabrang be trouble in propagation. For that purpuse bulbs divisionaimed to decreasing bulb needed and the right comparing of planting media can increase growthand yield of bawang sabrang. This research was conducted in experimental field at Jl. Pembangunanin April- July 2013, used randomized block design with two factor etc bulb division (no division, 2part division, 4 part division) and comparing planting media (topsoil, topsoil+compost 1:1, 2:1,3:1). Parameter observed was germination time, plant height, number of leaves, number of bulbs persample, fresh bulb weight per sample and fresh bulb weight per plot.The result of this researhshowed that bulb division significantly decreased germination time, plant height, number of bulbsper sample, fresh bulb weight per sample and fresh bulb weight per plot.Comparing of plantingmedia significantly effect number of leaves, number of bulbs per sample, fresh bulb weight persample and fresh bulb weight per plot. Interaction between bulb division and comparing plantingmedia significantly number of leaves, number of bulbs per sample, fresh bulb weight per sampleand fresh bulb weight per plot. The best result showed in no division and comparing planting media1:1 and 2:1.Keyword : bulb division, comparing of planting media, bawang sabrang